2001
DOI: 10.1093/ije/30.6.1371
|View full text |Cite
|
Sign up to set email alerts
|

Validation of self-reported hearing loss. The Blue Mountains Hearing Study

Abstract: In this older population with a high prevalence of hearing loss (39.4%), both a question about hearing and the HHIE-S appeared sufficiently sensitive and specific to provide reasonable estimates of hearing loss prevalence. Both could be recommended for use in epidemiological studies that aim to assess the magnitude of the burden caused by age-related sensory impairment but cannot measure hearing loss by audiometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
355
13
19

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(411 citation statements)
references
References 19 publications
(23 reference statements)
24
355
13
19
Order By: Relevance
“…The assessment of hearing loss through self reference is susceptible to the elderly perception for the presence of this deficit, which involves issues such as life experience, culture, education, the context in which it is inserted, in addition to the specific characteristics of presbycusis. On the other hand, the validity of this type of hearing assessment has been widely investigated, and the findings reveal good performance and high sensitivity in identifying hearing loss [20][21][22][23] . Ferrite, Santana and Marshall 24 checked the validity of three generic questions to assess self-reported hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of hearing loss through self reference is susceptible to the elderly perception for the presence of this deficit, which involves issues such as life experience, culture, education, the context in which it is inserted, in addition to the specific characteristics of presbycusis. On the other hand, the validity of this type of hearing assessment has been widely investigated, and the findings reveal good performance and high sensitivity in identifying hearing loss [20][21][22][23] . Ferrite, Santana and Marshall 24 checked the validity of three generic questions to assess self-reported hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The Blue Mountains population-based cohort study, in Sydney, the prevalence rates of self-reported hearing loss in the elderly was 39.4% 23 . In Beaver…”
mentioning
confidence: 99%
“…Results have been satisfactory when compared to the results of audiology tests 27,28 . In Brazil, the HHIE has shown itself to be a highly sensitive and specific auditory screening test, capable of identifying hearing loss in the elderly who come into the healthcare service 29 .…”
Section: Discussionmentioning
confidence: 74%
“…No entanto, devido ao custo e dificuldades logísticas para sua detecção precoce em nível populacional, a deficiência auditiva referida mostra-se como um ótimo instrumento de triagem auditiva (Valete-Rosalino e Rozenfeld, 2005; Santiago e Novaes, 2009) e tem sido utilizada por muitos pesquisadores (Jones, Victor e Vetter, 1984;Coelho Filho e Ramos, 1999;Sindhusake et al, 2001;Castro et al, 2008;Cruz et al, 2009;Paiva et al 2011;Cruz et al, 2012;Airoldi et al, 2013;Crispim e Ferreira, 2015). A partir desse tipo de triagem, espera-se aumentar a chance de uma pessoa com determinada disfunção ser identificada e de não considerar aquela sem disfunção (Valete-Rosalino e Rozenfeld, 2005).…”
Section: Alterações Otológicas Decorrentes Do Envelhecimentounclassified
“…Enquanto uns perguntavam se o entrevistado ouvia bem ou se apresentava dificuldades para ouvir (Jones, Victor e Vetter, 1984;Sindhusake et al, 2001;Castro et al, 2008;Souza e Oda, 2008;Cruz et al, 2009;Gutierrez et al, 2009, Paiva et al, 2011Airoldi et al, 2013), outros questionavam a existência de dificuldades para compreender a fala (Airoldi et al, 2013 Paiva et al, 2011).…”
Section: Prevalência E Causas Atribuídas à Deficiência Auditiva Referunclassified